KELEMBAGAAN PENDIDIKAN DI INDONESIA - Widiyanti, Widiyanti; Kartika, Yuni; Oktaviana, Fauzia; Fauzi, Diki Ahmad; Mufliyah, Azkia Naufal; Sonya, Endah Ratna (IBERS : Jurnal Pendidikan Indonesia Bermutu, 2024)
One factor that significantly influences the quality of education is the organization or institution providing the education. This problem has an impact on the training management process being inefficient and ineffective. The research method used is a qualitative descriptive method where library materials are collected, reading materials and notes are taken, and research materials are processed. Education is a lifelong process of practice and event that involves spontaneous and systematic reflection. The essence of education is to bring out human intelligence (humanization).